Boosting Sales through WhatsApp Business and Service Quality: The Mediating Role of Customer Satisfaction at CV. Bhakti Jaya Indonusa (BJI Advertising) - Sujaya, Indra; Elfiswandi, Elfiswandi; Lusiana, Lusiana (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study aims to determine the Increase in Sales: Whatsapp Business and Service Quality with Customer Satisfaction as an Intervening Variable at CV. Bhakti Jaya Indonusa (BJI Advertising). The method used is multiple linear regression analysis and path analysis, with a sample of 100. The results of the study show a significant effect of whatsapp business on customer satisfaction at CV. Bhakti Jaya Indonusa (BJI Advertising). There is a significant effect of service quality on customer satisfaction at CV. Bhakti Jaya Indonusa (BJI Advertising). There is a significant effect of whatsapp business on increasing sales at CV. Bhakti Jaya Indonusa (BJI Advertising). There is a significant effect of service quality on increasing sales at CV. Bhakti Jaya Indonusa (BJI Advertising). There is a significant effect of customer satisfaction on increasing sales at CV. Bhakti Jaya Indonusa (BJI Advertising). Customer satisfaction is able to mediate the effect of whatsapp business on increasing sales at CV. Bhakti Jaya Indonusa (BJI Advertising). Customer satisfaction is able to mediate the effect of service quality on increasing sales at CV. Bhakti Jaya Indonusa (BJI Advertising).